2018
DOI: 10.4067/s0718-33052018000300440
|View full text |Cite
|
Sign up to set email alerts
|

Properties and in-service performance of components reated with thermo reactive deposition/diffusion

Abstract: Properties and in-service performance of components reated with thermo reactive deposition/diffusionPropiedades y desempeño en servicio de componentes tratados con deposición/difusión termorreactiva ABSTRACT Machine components and tools subjected to aggressive environments and strong wear conditions need surfaces with good mechanical properties. The thermo-reactive deposition/diffusion (TRD) process is one of the methods used for improving the mechanical properties of these components and tools, mainly because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In many applications, tool steels are coated with transition metal carbides to improve corrosion resistance. Some authors report the improvement in the corrosion resistance of AISI D2 (111,112,113,114,115,116,117) and AISI H13 115) tool steel with the production of a layer of chromium niobium carbide on the steel surface, and other works have reported that for tool steels the corrosion behavior could be more influenced by its phase composition that the nanocrystalline structure (118) .…”
Section: Tool Steelsmentioning
confidence: 99%
“…In many applications, tool steels are coated with transition metal carbides to improve corrosion resistance. Some authors report the improvement in the corrosion resistance of AISI D2 (111,112,113,114,115,116,117) and AISI H13 115) tool steel with the production of a layer of chromium niobium carbide on the steel surface, and other works have reported that for tool steels the corrosion behavior could be more influenced by its phase composition that the nanocrystalline structure (118) .…”
Section: Tool Steelsmentioning
confidence: 99%